(untitled) (Research, Society and Development, 2023)
The beginning of the commercialization of electronic cigarettes in the international market occurred in 2007, gaining space among adolescents and young adults with the promise that it would be a “healthier” alternative. However, it is not without side effects. Thus, the present work is a literature review, whose objective was, through scientific studies already published, to gather scientific information for the contribution and construction of the proposed theme. The research was carried out in November 2022, through an online search of articles indexed in the databases of the Scielo platform, Google Scholar and Pubmed. Initially, the search was carried out on the Scielo website, using the descriptors lung injuries AND electronic cigarettes; lung lesions AND histology, a total of 12 articles were detected, during the years 2014 to 2021. On the Google Scholar platform, a total of 296 articles were published according to the respective descriptors. On the Pubmed platform, it was possible to detect an increase in publications with a total of 310 articles, totaling 618 publications. It was observed that the mechanisms of lung damage triggered by the use of electronic cigarettes are not yet well understood, but it is known that the inhalation of cigarette smoke with nicotine and other toxic substances can result in the infiltration of inflammatory cells of the mucosa, submucosa and glandular tissue. Thus, the present work proved to be relevant for obtaining information on lesions in the pulmonary system and levels of toxicity associated with the use of electronic cigarettes.